Bibliometric Analysis of Green Marketing Strategies: Innovative Approaches to Improve Sustainability - Saputra, Apep Indra; Asfiah, Nurul (Ann Publisher, 2025)
Sustainability has become an urgent global issue, and green marketing emerges as a crucial strategy to support environmentally friendly business practices. This study aims to identify research trends in the field of green marketing through bibliometric analysis using the VOSviewer tool. The data used were sourced from Scopus-indexed publications between 2014 and 2024, with the main identified themes being green consumption development, environmental awareness, and green supply chain management. The findings indicate that although green marketing raises consumer awareness of eco-friendly products, there is a gap between purchase intentions and actual consumer behavior. This study also highlights the importance of clear information and effective communication to enhance loyalty to green brands. Additionally, collaboration among companies, consumers, and governments is essential to achieving broader sustainability in the context of green marketing and consumption.